The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1080/09585192.2011.606124
|View full text |Cite
|
Sign up to set email alerts
|

Having two bosses: considering the relationships between LMX, satisfaction with HR practices, and organizational commitment

Abstract: The current study went beyond previous research on leader-member exchange (LMX) by examining employees who are supervised by more than one boss. Using data from 122 PhDs from a Dutch university, the current study had three research objectives. First, to examine the effects of PhDs' LMX with both their promoter and their assistant promoter on affective organizational commitment (AOC). Second, to examine the mediating role of satisfaction with HR practices in the two LMX -AOC relationships. Since the promoter as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…The tests confirmed the results of many earlier studies [18,[19][20][21][22] that LMX and commitment are significantly positively correlated. Further, analysis revealed that respondents with high quality LMX are more committed to the organization's values [positive correlation] and have lower level of commitment to stay [negative correlation].…”
Section: Discussion Of the Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The tests confirmed the results of many earlier studies [18,[19][20][21][22] that LMX and commitment are significantly positively correlated. Further, analysis revealed that respondents with high quality LMX are more committed to the organization's values [positive correlation] and have lower level of commitment to stay [negative correlation].…”
Section: Discussion Of the Resultssupporting
confidence: 81%
“…Some scholars already emphasized the important connections between LMX and organizational commitment [18,[19][20][21][22]. However, most researches do not reveal anything deeper than the simple notation that LMX correlates with organizational commitment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, satisfaction with HR practices has been found by Yousaf et al. () to fully mediate the relationship between LMX and organizational commitment. In the current research, the relationship between the perceived efficacy of DM and organizational commitment is not simple and straightforward.…”
Section: Development Of Hypothesesmentioning
confidence: 95%
“…Hypothesis 3: Contribution has a positive effect on affective commitment to change. Hypothesis 4: Professional respect has a positive effect on affective commitment to change The relationship between superiors and subordinates is related to employee self-efficacy, where subordinates who feel the relationship quality with the superiors is high feel the support of the leader [3] and more rewards, positive feedback from leaders [19], as well as feeling a sense of belonging, and as a form of exchange members will show through commitment [20]. In the situation of change, superiors need to support their subordinates' beliefs about the change in the organization [13] because subordinates' self-efficacy influences their choices in behavior.…”
Section: Leader-member Exchange Change Self-efficacy and Affective mentioning
confidence: 99%